2015
DOI: 10.1111/apt.13232
|View full text |Cite
|
Sign up to set email alerts
|

Patatin‐like phospholipase 3 (rs738409) gene polymorphism is associated with increased liver enzymes in obese adolescents and metabolic syndrome in all ages

Abstract: SUMMARY BackgroundObesity is associated with non-alcoholic fatty liver disease (NAFLD), and the patatin-like phospholipase 3 (PNPLA3) rs738409 (Ile148Met, C>G) gene polymorphism is one of the most important genetic determinants of NAFLD. Carriers have been reported to better respond to lifestyle modification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
36
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 32 publications
1
36
0
1
Order By: Relevance
“…NAFLD is the most common liver disease in children and adolescents (Table 2). Similarly to adult patients, NAFLD is associated with obesity and metabolic syndrome 27 and probably with elevated alanine aminotransferase (ALT) levels in blood and PNPLA3 polymorphisms 28 ( Figure 1) 29 . A recent analysis of the National Health and Examination Survey, including data from >12,000 12-19 year-old Americans, showed that NAFLD prevalence (with NAFLD defined as BMI > 85 th percentile and elevated ALT levels of >22.1 U/L for girls and >25.8 U/L for boys) more than doubled over the past two decades 27 .…”
Section: [H2] Children and Adolescentsmentioning
confidence: 99%
“…NAFLD is the most common liver disease in children and adolescents (Table 2). Similarly to adult patients, NAFLD is associated with obesity and metabolic syndrome 27 and probably with elevated alanine aminotransferase (ALT) levels in blood and PNPLA3 polymorphisms 28 ( Figure 1) 29 . A recent analysis of the National Health and Examination Survey, including data from >12,000 12-19 year-old Americans, showed that NAFLD prevalence (with NAFLD defined as BMI > 85 th percentile and elevated ALT levels of >22.1 U/L for girls and >25.8 U/L for boys) more than doubled over the past two decades 27 .…”
Section: [H2] Children and Adolescentsmentioning
confidence: 99%
“…PNPLA3 gene polymorphism is the most widely studied genetic determinant of NAFLD . The at‐risk GG genotype is associated with a 2‐ to 3‐fold increase in the risk of NAFLD.…”
Section: Discussionmentioning
confidence: 99%
“…PNPLA3 gene polymorphism is the most widely studied genetic determinant of NAFLD. [47][48][49] The at-risk GG genotype is associated with a 2-to 3-fold increase in the risk of NAFLD. In our study, the endotoxin biomarkers and fetuin-A level did not differ in subjects with different PNPLA3 genotypes.…”
Section: Discussionmentioning
confidence: 99%
“…NAFLD is the most common liver disease in children and adolescents ( Table 2). Similarly to adult patients, NAFLD is associated with obesity and metabolic syndrome 27 and probably with elevated alanine aminotransferase (ALT) levels in blood and PNPLA3 polymorphisms 28 ( Figure 1) 29 . A recent analysis of the National Health and Examination Survey, including data from >12,000 [12][13][14][15][16][17][18][19] year-old Americans, showed that NAFLD prevalence (with NAFLD defined as BMI > 85 th percentile and elevated ALT levels of >22.1 U/L for girls and >25.8 U/L for boys) more than doubled over the past two decades 27 .…”
Section: [H2] Children and Adolescentsmentioning
confidence: 99%